Microstructural, Tribological, and Degradation Properties of Al2O3- and CeO2-Doped 3mol.% Yttria-Stabilized Zirconia Bioceramic for Biomedical Applications - Golieskardi M.; Satgunam M.; Ragurajan D.; Hoque M.E.; Ng A.M.H. (Springer, 2023)
Alumina; Aluminum oxide; Body fluids; Cerium oxide; Fracture toughness; Medical applications; Sintering; Temperature; Tribology; Yttria stabilized zirconia; Yttrium oxide; Zirconia; Bioimplant applications; Biomedical applications; Degradation patterns; ITS applications; Low-temperature degradations; Relative density; Stabilized zirconia; Theoretical density; Bioceramics